Development of permethrin resistance in Culex quinquefasciatus Say in Kuala Lumpur, Malaysia - Wan-Norafikah, Othman; Nazni, W.A.; Lee, H.L.; Zainol-Ariffin, P.; Sofian-Azirun, Mohd (2013)
The resistance status towards permethrin among the laboratory strain, the permethrin-selected strain and four field strains of Culex quinquefasciatus collected in Kuala Lumpur, Malaysia was determined using three standard laboratory methods: WHO larval bioassay, WHO adult bio-assay and biochemical microplate assay. Cx. quinquefasciatus permethrin-selected strain larvae were the least susceptible to permethrin with a resistance ratio of 47.28-folds, whereas all field strain larvae of the same species were tolerant to permethrin with resistance ratios of more than 3-folds. In contrast, in adult stage, the permethrin exposed permethrin-selected strain (resistance ratio = 1.27) was found to be more susceptible to permethrin than all permethrin-exposed field strains (resistance ratios = 2.23-2.48). Complete mortalities for all strains of Cx. quinquefasciatus adults proved the effectiveness of the synergist; piperonyl butoxide (PBO). For the biochemical microplate assay, the reduction of the mean optical density of elevated oxidase activity of three field strains upon exposure to PBO confirmed the association between oxidase activity and permethrin tolerance. On the other hand, irregular patterns of the mean optical density of elevated oxidase activity in the laboratory strain, permethrin-selected strain and Jalan Fletcher strain illustrated the gene variation within these mosquito colonies as well as the involvement of other enzyme activities in the permethrin resistance occurred. (C) 2013 Production and hosting by Elsevier B.V. on behalf of King Saud University.